Fluorescent Capillary Electrophoresis Is Superior to Culture in Detecting Candida Species from Samples of Urinary Catheters and Ureteral Stents with Mono- or Polyfungal Biofilm Growth - Obručová, Hana; Kotásková, Iva; Tihelková, Radka; Holá, Veronika; Růžička, Filip; Freiberger, Tomáš (Journal of clinical microbiology, 2019)
Molecular techniques in fungal detection and identification represent an efficient complementary diagnostic tool which is increasingly used to overcome limitations of routinely used culture techniques. The aim of this study was to characterize Candida sp. representation in samples from urine, urinary catheter, and ureteral stent biofilm using ITS2 ribosomal DNA (rDNA) amplification followed by fluorescent capillary electrophoresis (f-ITS2-PCR-CE) and to compare the results with those obtained by culture. A total of 419 samples were analyzed, and 106 (25.2%) were found positive, out of which 17 (16%) were polyfungal. The positivity rate did not differ between samples from catheters and stents (23.6% versus 20.9%) or between catheter and stent corresponding urine samples (40.2% versus 30.2%). Ten different Candida species were detected, with Candida parapsilosis (31.4%), Candida albicans (26.5%), and Candida tropicalis (12.4%) predominating. f-ITS2-PCR-CE was evaluated as substantially less time-consuming and 8.3 times more sensitive than the routinely applied culture technique with 1 µl of urine/sonicated fluid inoculated, detecting 67 (19.9%) versus 8 (2.4%) positive samples out of 337 initially analyzed samples. The culture sensitivity considerably improved to 1.7 times lower than that of f-ITS2-PCR-CE after the inoculation volume was increased to 100 µl in the additional 82 samples. Moreover, the molecular technique, unlike routine cultivation, enabled precise pathogen composition determination in polymicrobial samples. In conclusion, the f-ITS2-PCR-CE method was shown to be a quick and efficient tool for culture-independent detection and identification of fungi in urinary tract-related samples, demonstrating a higher sensitivity than culture.
Keywords: fluorescence; Candida parapsilosis; Candida tropicalis; Candidiasis; Candida albicans; ribozomální DNA; Female; DNA, Ribosomal; Electrophoresis, Capillary; polyfungal sample; elektroforéza kapilární; ženské pohlaví; Urinary Catheters; panfungal PCR; lidé; fungi; Molecular Diagnostic Techniques; DNA, Fungal; počet mikrobiálních kolonií; Sensitivity and Specificity; biofilms; capillary electrophoresis; urinary catheters; senzitivita a specificita; Colony Count, Microbial; Male; diagnostické techniky molekulární; Aged; Stents; močové katétry; kandidóza; DNA fungální; Candida; Fluorescence; biofilmy; senioři; mužské pohlaví; ureteral stents; Biofilms; stenty; Humans